Coupling Effect of Strain Rate and Freeze-Thaw Temperature on Dynamic Mechanical Properties and Fractal Characteristic of Saturated Yellow Sandstone. (26th September 2021) - Wu, Peng; Zhang, Lianying; Mao, Xianbiao; Chen, Yanlong; Li, Ming; Chen, Liang; Wang, Lan
Abstract : Strain rate is not only an important influence factor for deformation property but also an important parameter for analyzing the dynamic mechanical behavior of rock material. In this study, the dynamic compressive mechanical properties of saturated yellow sandstone at four strain rates and six freeze-thaw temperatures are investigated by using the SHPB test system. The coupling effect of strain rate and freeze-thaw temperatures on the mechanical parameters of rock material are discussed in detail, and the relationship formula of peak strain and dissipated energy with strain rate and freeze-thaw temperature are also established. Finally, the fractal dimension characteristic of fracture specimens with the strain rate and temperature are analyzed by using the fractal dimension method. The research results indicate that (1) with the increase of strain rate, the increase speed of peak strain, peak strength, and dissipated energy at medium strain rate level was obviously higher than that at high strain rate level, indicating that the strain rate effect weakened at high strain rate. (2) Freeze-thaw temperature can improve the brittleness-ductile transformation rate of saturated specimens. (3) According to the strain rate sensitivity coefficient, at room temperature, the strain rate effects on peak strain and peak strength are weakest, while at -20°C -30°C, they are most significant. In addition, the strain rate effect on dissipated energy is significant at room temperature, while weakest at -30°C. (4) The fractal dimension gradually increases with strain rate increasing or freeze-thaw temperature decreasing, indicating that the freeze-thaw environment has a positive function for increasing the damage and fracture degree of specimens for saturated specimen. Our research results can provide an extremely important theoretical basis for the dynamic disaster prevention and structural design of rock engineering in cold regions.